Polyfunctional properties of goat colostrum proteins and their use - Soloshenko, Kateryna; Lych (Tkachenko), Inna; Voloshina, Iryna; Shkotova, Lyudmila (My University, 2020)
The review presents the composition of goat colostrum, antimicrobial, immunomodulatory and antioxidant properties of biologically active proteins of goat colostrum, as well as the prospects of their use in medicine. Due to the presence of a complex of biologically active proteins such as lactoferrin, lysozyme, lactoperoxidase, immunoglobulins, etc., goat colostrum increases the body’s resistance to infectious diseases, strengthens the immune system, has an antioxidant effect and antibacterial activity against a wide range of microorganisms, thereby preventing or delaying chronic diseases associated with the oxidative stress. Additionally, goat colostrum bioactive proteins show antitumor activity, antiatherogenic properties, the ability to lower the blood pressure and efficiency in the treatment of rheumatoid arthritis.
Keywords: colostrum; молозиво; protein complex; білковий комплекс; antimicrobial action; антимікробна дія; immunomodulator; імуномодулятр; antioxidant; антиоксиданти; кафедра біотехнології і мікробіології